Impact of nutritional guidance on various clinical parameters in patients with moderate obesity: A retrospective study - Kayoko Oda; Kayoko Oda; Takatoshi Anno; Nozomi Ogawa; Nozomi Ogawa; Yukiko Kimura; Fumiko Kawasaki; Kohei Kaku; Hideaki Kaneto; Mutsuko Takemasa; Miyori Sasano; Miyori Sasano (Frontiers in Nutrition, 2023)
ContextThis study aims to investigate whether there is adequate provision of nutritional guidance through interventions by registered dietitians, especially for patients with moderate obesity. This is particularly important as such interventions may prove to be more effective for Japanese patients.MethodsIn Japan, since there is a system of nutritional guidance with a registered dietitian for patients with a BMI over 30 kg/m2, we recruited 636 patients with obesity who had a BMI over 30 kg/m2 admitted to the Kawasaki Medical School General Medical Center between April 2018 and March 2020 through a review of their medical records. Second, we recruited 153 patients who underwent a blood examination before receiving nutritional guidance and at least one time every 3 to 6 months thereafter after receiving it. We aimed to evaluate whether continued nutritional guidance and follow-up interventions for patients with obesity were effective. We compared the BMI and metabolic markers of the patients who received nutritional guidance from a registered dietitian against those who did not.ResultsA total of 636 patients with obesity who have a BMI over 30 kg/m2 were included in this study. A total of 164 patients with obesity received nutritional guidance from a registered dietitian at least one time, but 472 patients did not. Most interventions on nutritional guidance conducted by a registered dietitian were ordered from internal medicine (81.1%). However, internal medicine was the most common department that did not perform these interventions; however, less than half of the (49.2%) received them. In the second analysis, we compared two groups of patients with obesity. The first group (n = 70) who underwent blood examinations received nutritional guidance from a registered dietitian, while the second group (n = 54) did not receive such guidance. We found that there was no significant difference in body weight and BMI between the two groups of patients. We observed a significant decrease in dyslipidemia-associated metabolic markers among the patients who received nutritional guidance compared to those who did not [total cholesterol, −9.7 ± 29.3 vs. 2.3 ± 22.0 mg/dL (p = 0.0208); low-density lipoprotein cholesterol, −10.4 ± 30.5 vs. −2.0 ± 51.0 mg/dL (p = 0.0147), respectively]. Other metabolic markers also tended to decrease, although they did not reach statistical significance.ConclusionIt is rare for patients with only obesity to receive nutritional guidance. However, when nutritional guidance from a registered dietitian is provided, improvements in BMI and metabolic parameters can be expected.